Relations entre l’estime de soi et l’état de santé « objectif » des aînés - Enguerran Macia; Gilles Boëtsch; Nicole Chapuis-Lucciani (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In spite of several studies on self-esteem covering the human life-span, the relation between self-esteem, aging and health remains incompletely explored, particularly in the French population.The objective of this study is twofold: (1) to assess the relation between self-esteem and socio-demographic factors, notably age, among older French adults, and (2) if, as is presumed, advancing age is associated with lower self-esteem, to test the mediating effect of chronic diseases and physical incapacities on the relation between age and negative self-esteem.For this, 400 older adults living in Marseille, aged from 60 to 92, were individually interviewed (average duration: 1 h 30).In this sample, age, place of residence and educational level were associated with self-esteem. Physical incapacities were also associated with self-esteem, but chronic diseases were not. Our analyses showed that the relationship between advancing age and negative self-esteem is not direct, but mediated by physical incapacities. On the other hand, and without dichotomizing self-esteem, analysis of cause indicates that the relation between age and self-esteem (entered in the model as a continuous variable) was mediated by physical incapacities and institutionalization.These results are discussed through the social activities theory, and through power relationships inherent in dependency.